KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA SEKOLAH EFEKTIF DI SEKOLAH DASAR - Farida, Farida (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2024)
This study aims to analyze the style and role of principal leadership in an effort to develop an effective school culture. This type of research is a case study conducted at SD Islam Terpadu Darul Qalam Jakarta (DAQTA). Data collection techniques used were interviews, observation and documentation. Data analysis techniques used are: (1) data reduction; (2) presentation of data; And (3) conclusions. Test the validity of the data through the test: (1) credibility; (2) transferability; (3) dependability; (4) confirmability. The results of this study indicate that (1) the principal does not only apply one particular leadership style, but according to the conditions at hand. (2) The role of the principal in developing an effective school culture is as an educator, manager, administrator, supervisor, leader, innovator and motivator. (2) The Headmaster’s efforts in developing an effective school culture are: (a) Developing harmonious relationships among all school components, (b) Developing school security, (c) Developing a school environment conducive to learning